Clinical features of pituitary carcinoma: analysis based on a case report and literature review - Yang, Yongxiang; Liang, Wanlin; Fan, Kexia; Yang, Tao; Cheng, Jingmin (Frontiers in Endocrinology, 2024)
Introduction Pituitary carcinoma (PC) is an extremely rare tumor of the adenohypophysis, which manifests as craniospinal dissemination and/or systemic metastasis. The diagnosis of PC is particularly difficult, as the clinical diagnosis only can be made after the metastasis is found. Owing to the complex diagnostic process and less effective treatments, the clinical prognosis of PC is usually very poor. Hence, it is of great significance to illustrate the diagnosis and treatment course of PC. Methods In this case report, we described a 48-year-old male patient who was diagnosed with pituitary adenoma (PA) initially and then was diagnosed with PC eventually after spinal cord metastasis was found, and we illustrated the treatment course as well. Furthermore, we summarized all the published case reports until now and provided a comprehensive review of the diagnosis, treatment, prediction, and clinical outcome of PC. Results and Conclusions We found that most PC patients had adrenocorticotropic hormone/prolactin (ACTH/PRL)-secreting tumors, Ki-67 ≥ 10%, and P53 positivity, which may have the potential to predict the transformation from PA to PC; surgery excision combined with temozolomide (TMZ) and radiotherapy is helpful to prolong the survival of PC patients.